“Penggunaan Flip Book Terhadap Peningkatan Hasil Pembelajaran Bahasa Inggris Siswa pada Aspek Kognitif Tingkat Rendah (Quasi Eksperimen Pokok Bahasan Tenses pada Siswa Kelas XII Semester I di SMAN 16 Garut)” - teten mohamad sapril mubarok (Institut Pendidikan Indonesia, 2021)
The research was conducted in an effort to find out the differences between students who were taught by using Flip book and those who were taught without using the Flip book in mastery of low level of cognitive aspects. This research design was a quasi-experimental using two groups. In the experimental group was applied the learning process of learning media flipbook while the control group it was not applied the learning media flipbook. The Subjects in this study were 35 students of XII IPA 5 class as an experimental class and 35 students of XII IPA 4 as the control class in SMAN 16 Garut. The research Result showed that: (1) The Mastery of the cognitive aspects of low-level concept of tenses in English Language Learning in SMAN 16 Garut before it was given the study treatment by applying the learning media flipbook in the learning process are at low qualifying on aspects of knowledge, understanding and aspects of the application, (2) The mastery of Cognitive low-level Aspects of tenses in English Language Learning in SMAN 16 Garut after applying research treatment increased. Classes that implement instructional media flipbook increased on aspects of knowledge into high qualifications, aspects of the understanding and application increased into medium qualification, whereas classes that did not implement instructional media flipbook, aspect of knowledge and understanding increased into medium qualification and low qualifying for aspects of the application , (3) There were significant different increase in the cognitive aspects of low-level in mastery of the concept of tenses between students who learn by applying the learning media flipbook with students who learnt without implementing instructional media flipbook in English learning at XII IPA class at SMAN 16 Garut. Keywords: Flipbook, Cognitive Aspects of Learning Outcomes, tenses, English Language Learning.